Morpheme in Arabic Morphology - A‘l Warkash, Wadha Ahmed Musa'ad (Arab Journal for Sciences and Research Publishing, 2018)
The study aimed to identify the definition and several types of morpheme, and examine its usage in Arabic language, also its role and value in Arabic morphology. The study used qualitative methodology by analyzing the concept and definition of morpheme. The findings revealed that Language specialist’s identified morpheme as a concept of morphology analysis and the smallest concept that carries a meaning, also, the construct of the word is very essential to understand the meaning of the word, and ancient Arabs pointed to morpheme concept and its important role in the language construct. Moreover, the Arabic language is considered flexible and it includes derivatives in its vocabulary, also, sometimes morphological and grammatical morpheme can give the same meaning in the language and both could be inseparable. The usage of the morpheme could be limited to certain places in the language or unlimited, this depends on its form and the purpose it serves, as it used for count, time and type.